The Role of Brand Ambassadors on Consumer Purchase Decision on Tokopedia Marketplace - Risania S Timpal; James Massie; Merinda Pandowo (Universitas Sam Ratulangi, 2022)
The purpose of this research is to find out the role of brand ambassadors on consumer purchase decision on Tokopedia marketplace. This research used Qualitative method and there were 15 informants who are domicile in North Sulawesi and confirmed to be affected by the ambassadors, they have been interviewed in order to get the result by using VisCAP (Visibility, Credibility, Attraction, and Power) Model by Rossiter and Percy as the indicators. This research shows that mostly the informants bought products on Tokopedia because of the Power, Attraction, and Credibility of the brand ambassadors, and none of them is being affected by the Visibility. To make it more specific, the informants bought things from Tokopedia to get the limited photo card of the brand ambassadors and to support their idol as the loyal fans (Power), they also bought things from Tokopedia because they find the brand ambassadors attractive (Attraction), and the last one, they bought products from Tokopedia because the brand ambassadors are professional in delivering the massage and pursuing the consumer to buy from Tokopedia (Credibility).